Improving Teachers’ Organizational Citizenship Behavior Based on Emotional Intelligence and Psychological Capital - Widodo, Widodo; Sulistiasih, Sulistiasih (Jurnal Pendidikan Progresif, 2023)
Improving Teachers’ Organizational Citizenship Behavior Based on Emotional Intelligence and Psychological Capital. Objectives: This study investigates the effect of emotional intelligence on teachers’ psychological capital (PsyCap) and organizational citizenship behavior (OCB) and how PsyCap mediates emotional intelligence in affecting OCB. Methods: A questionnaire on the Likert rating scale collected data through the survey methods from 250 junior high school teachers in Indonesia. Data analysis uses path analysis supported by descriptive and correlational analysis. Path analysis was performed by Lisrel 8.80, meanwhile descriptive and correlational analysis by SPSS 22. Finding: Emotional intelligence had a significant effect on teachers’ OCB, directly and indirectly, mediated by PsyCap. Besides mediating the effect of emotional intelligence on teachers’ OCB, PsyCap also has a direct effect strongly than emotional intelligence. Hence, it shows the cruciality PsyCap for teachers’ OCB. Conclusion: A model regarding the effect of emotional intelligence on teachers’ OCB, mediated by PsyCap, was confirmed. Accordingly, the researchers and practitioners can discuss, adapt, and adopt an empirical model to improve teachers’ OCB based on emotional intelligence and PsyCap in various researchs fields in the future. Keyword: emotional intelligence, psychological capital, organizational citizenship behavior.DOI: http://dx.doi.org/10.23960/jpp.v13.i1.202305